2020
DOI: 10.1097/gme.0000000000001655
|View full text |Cite|
|
Sign up to set email alerts
|

lncRNA HEIH accelerates cell proliferation and inhibits cell senescence by targeting miR-3619-5p/CTTNBP2 axis in ovarian cancer

Abstract: Objective: Epithelial ovarian cancer is the most lethal malignancy in gynecology. Numerous studies have confirmed that long noncoding RNAs (lncRNAs) are abnormally expressed in ovarian cancer and are closely associated with the cell proliferation and senescence in cancers. However, the role and underlying molecular mechanism of long noncoding RNA high expression in hepatocellular carcinoma (HEIH) in ovarian cancer remain unknown. Methods: Experiments in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…These results suggest that high expression of lncRNA HEIH predicts poor prognosis in patients with NSCLC. The expression of HEIH is up-regulated in ovarian cancer tissues and cell lines, and high expression of HEIH indicates a poor prognosis [25]. Oesophageal squamous cell carcinoma patients with high lncRNA HEIH expression have poorer prognosis than those with low expression [26].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that high expression of lncRNA HEIH predicts poor prognosis in patients with NSCLC. The expression of HEIH is up-regulated in ovarian cancer tissues and cell lines, and high expression of HEIH indicates a poor prognosis [25]. Oesophageal squamous cell carcinoma patients with high lncRNA HEIH expression have poorer prognosis than those with low expression [26].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, elevated HEIH expression was related to poor prognosis. Mechanically, HEIH accelerated cell proliferation, migration and invasion, whereas inhibited cell senescence via targeting the miR-3619-5p/CTTNBP2 axis [ 44 ]. It is tempting to conclude that bias towards up-regulation of HEIH in cancer may results from the above large-scale practice discovering HEIH from various cancer samples.…”
Section: Heih In Various Human Cancersmentioning
confidence: 99%
“…Coherently with this function, HEIH was found to promote malignant phenotypes by competitively binding miR-4458 to upregulate the expression of SOCS1and PBX3 in breast cancer and esophageal cancer, respectively [ 33 , 51 ]. Similarly, HEIH triggered ovarian cancer and tongue squamous cell carcinoma development by sponging miR-3619-5p, and consequently upregulating the miR-3619-5p targets CTTNBP2 and HDGF [ 28 , 44 ]. Nafea et al and Cui et al showed HEIH could directly interact with miR-939 to counteract the effects of miR-939 on the transcription of Bcl-xl in colorectal cancer [ 64 ] and the production of NO 2 in TNBC [ 52 ].…”
Section: Mechanistic Model Of Heih In Human Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Long noncoding RNAs (lncRNAs) are a class of noncoding RNAs with a length of more than 200 nucleotides. Several lncRNAs have been confirmed to be deregulated and act as critical regulators in OC ( 4 ). Overexpression of lncRNA HOTTIP promoted the growth and metastasis of OC via the miR-615-3p/SMARCE1 axis ( 5 ).…”
Section: Introductionmentioning
confidence: 99%